Digital core analysis: Improved connectivity and permeability characterization of thin sandstone layers in heterolithic rocks. (October 2020) - Hasnan, Hijaz Kamal; Sheppard, Adrian; Amir Hassan, Meor Hakif; Knackstedt, Mark; Abdullah, Wan Hasiah
Abstract: Heterolithic thin beds reservoirs contain significant amounts of hydrocarbons. We characterized the reservoir properties (sandstone connectivity, continuity and permeability) of sandstone layers in heterolithic rocks using three-dimensional imaging and analysis of heterolithic core plugs and mini plugs. The high-resolution three-dimensional models of the samples are smaller than a typical reservoir model grid block and similar the millimetre-to-centimetre beddings in heterolithic rocks. We find that the key to reservoir quality in heterolithic rocks is the connectivity and continuity of thin reservoir sandstone layers. Also, we show that these well connected and continuous thin sandstone layers have higher effective permeabilities that are comparable to a reference reservoir sandstone. These results can provide further information as to why some low resistivity heterolithic intervals with low net-to-gross values of the sandstone produced a significant amount of hydrocarbon despite lower production forecast based on well logs and core plug data. Determining the connectivity and continuity of thin sandstone layers is difficult due to limitations of well logs and core plug analysis that do not resolve and capture the connectivity of thin beddings. We show that 3-D Image Visualization is effective in characterizing the connectivity and continuity of thin sandstone layers in heterolithic rocks. Also, our Digital Core Analysis method computed permeability of thin sandstone layers in 3-D models of mini plugs representing thin sandstone layers in heterolithic core plugs. Our results represent information and reservoir properties at the millimetre-to-centimetre scale that are similar to the thickness of thin sandstone beddings in heterolithic rocks. Highlights: Digital core analysis computes permeability and porosity at millimetre scale. 3D Visualization characterizes connectivity and continuity of sandstone layers. Permeability and Porosity of Sandstone layers comparable to reservoir sandstone. Thin sandstone layers connectivity main factor to reservoir quality of heterolithic rocks.